Sleeping, Smoking, and Kidney Diseases: Evidence From the NHANES 2017–2018 - Wu, Chia-Chao; Wang, Han-En; Liu, Yi-Chun; Zheng, Cai-Mei; Chu, Pauling; Lu, Kuo-Cheng; Chu, Chi-Ming; Chang, Yu-Tien (Frontiers in Medicine, 2021)
Study Objectives: Smoking and sleep are modifiable factors associated with chronic kidney diseases. However, the interaction of smoking and sleep on renal function are still unclear. Therefore, we aimed to evaluate the interactive impacts of smoking and sleep on renal function. Methods: Data were obtained from the National Health and Nutrition Examination Survey. The study population were categorized into nine subgroups by smoking (smoking every day, sometimes and non-smokers recently) and sleep duration (short duration ≤6h, normal duration 6–9h, and longer duration ≥9 h on weekdays). Results: The study group with short sleep duration had significantly higher serum cotinine and hydrocotinine levels than the other two sleep groups. After adjusting of demographic characteristics (age, race, body mass index, and marital status), sleep quality (snoring or breathing cessation), and comorbidities (diabetes mellitus, hypertension, high cholesterol, anemia, congestive heart failure, coronary heart disease and stroke), non-smokers with short or long sleep duration had significant lower eGFR levels than the study group who smoked every day and slept ≤ 6h. The effects of sleep duration on eGFR levels varied with smoking status. For study group smoking every day, eGFR levels increased as sleep duration decreased, whereas for study group smoking sometimes, eGFR levels increased as sleep duration increased. The U-shaped effects of eGFR levels were observed among non-smokers that normal sleep duration was associated with better eGFR levels. Normal sleep duration was an important protective factor of renal function for non-smokers than smokers. Conclusions: The effects of sleep duration on eGFR levels varied with smoking status. Normal sleep duration was a protective factor and more crucial for nonsmokers than for smokers.